Uneven Temporalities of Modernity: The Portrayal of Modernisation in E. M. Forster’s Howards End and Füruzan’s 47'liler - Alkan, Burcu (Border Crossing, 2016)
Arguably a cultural consequence of the extensive societal transformation that is modernisation, the novel is a literary form that bears witness to, embodies and reveals its extent. Each literary tradition has its own version of the modern novel that seeks to make sense of the complexities of such an immense force. This paper compares two novels, E. M. Forster’s Howards End (1910) and Füruzan’s 47’liler (1974, Generation of ’47), in order to explore some of the similarities and differences between the English and Turkish literary responses to modernisation. The incentive for such an uncommon comparison comes from the uneven temporalities of the modernisation process in varying geographies that accentuate unique probabilities alongside general patterns. By choosing two temporally disparate novels from cultures that have differing experiences with modernity, it aims to challenge conventional approaches and encourage alternative perspectives in both literary traditions.